Automated 24-h cattle feeding behaviour analysis using Raspberry Pi, infrared imaging, and deep learning-based head position and ID classification - G. Wager-Jones; M. Butler; W.E. Harris; M. Rutter; E. Bleach; K. Behrendt (Biosystems Engineering, 2026)

Projected Methane Emissions From a Boreal Thermokarst Bog Are Sensitive to Carbon Substrate Availability, Distribution, and Transport Pathway Dominance - Benjamin C. Maglio; Ruth Rutter; Valeria Briones; Andrew Mullen; Chu‐Chun Chang; Joshua M. Rady; Tobey Carman; Colin Edgar; Eugénie S. Euskirchen; Jennifer D. Watts; Susan M. Natali; Elchin E. Jafarov; et al. (Global Change Biology, 2026)
Methane is a potent greenhouse gas, which traps significantly more heat than carbon dioxide over short timescales, but remains underrepresented in models used for projecting future climate scenarios, particularly in permafrost landscapes. Understanding methane dynamics in northern wetlands is critical for improving projections of high‐latitude carbon feedbacks to the global climate system. To address this, we integrated ecological processes driving methane production, oxidation, and transport pathways into the DVM‐DOS‐TEM terrestrial biosphere model. Using long‐term site observations from a thermokarst bog in boreal Alaska, we calibrated and benchmarked the model against observations of methane and carbon dioxide fluxes, carbon and nitrogen stocks, and soil temperature and moisture. Parameter sensitivity analyses identified opposing correlations for methanogenesis and heterotrophic respiration, revealing a dependence on carbon availability. We also found sensitivity to the distribution of carbon relative to the water table position. Investigation of the dominance of different methane transport pathways demonstrated the need for observations of methane flux partitioning, and the utility in comparing simulated to observed seasonality. The cumulative methane efflux projected to the year 2100 had a range of 211–3470 g C m −2 between low and high warming scenarios. Methane emissions dominated by diffusion showed the greatest variability across projections. Increased soil temperature and carbon availability from permafrost thaw resulted in increasing methane emissions between 2030 and 2060. But methane emission was then limited by a deepening of the water table. Nevertheless, we estimated a positive radiative forcing (i.e., warming) from these mid‐century methane emissions that persisted until 2100. An ebullition‐dominant parameterization led to lower variability but a net negative radiative forcing (i.e., cooling) on average. Our study highlights the importance of representing methane emission pathways and the uncertainty associated with partitioning them on predicting the carbon budget and radiative forcing of wetland ecosystems in high latitudes.

An exploratory spatial contaminant assessment for polar bear (Ursus maritimus) liver, fat, and muscle from northern Canada - V Boutet; M Dominique; KM Eccles; M Branigan; M Dyck; P van Coeverden de Groot; SC Lougheed; A Rutter; VS Langlois (Environmental Pollution, 2023)

Disrupting the disruptors: the consequences of mutations in mobile elements for ecologically important life history traits - Matthew T. Rutter; April M. Bisner; Clare Kohler; Keyaira Morgan; Olivia Musselman; Julia Pickel; Jerica Tan; Yuki Yamasaki; Jay Willson; Hilary S. Callahan; Allan E. Strand; Courtney J. Murren (Evolutionary Ecology, 2020)

Blood lipids and colorectal polyps: testing an etiologic hypothesis using phenotypic measurements and Mendelian randomization - Michael N. Passarelli; Polly A. Newcomb; Karen W. Makar; Andrea N. Burnett-Hartman; John D. Potter; Melissa P. Upton; Lee-Ching Zhu; Michael E. Rosenfeld; Stephen M. Schwartz; Carolyn M. Rutter (Cancer Causes & Control, 2015)

Temporal and spatial patterns in tumour prevalence in brown bullhead Ameiurus nebulosus (Lesueur) in the tidal Potomac River watershed ( USA ) - A E Pinkney; J C Harshbarger; M A Rutter (Journal of Fish Diseases, 2014)
For two decades, fish tumour surveys have been used to monitor habitat quality in the Chesapeake Bay ( USA ) watershed. Tributaries with sediments contaminated with polynuclear aromatic hydrocarbons ( PAH s), known to cause liver neoplasia, were frequently targeted. Here, we compare surveys in brown bullhead Ameiurus nebulosus conducted in 2009–2011 in the tidal Potomac River watershed (including the Anacostia River) with previous surveys. Using logistic regression, we identified length and sex as covariates for liver and skin tumours. We reported a statistically significant decrease in liver tumour probabilities for standardized 280 mm Anacostia bullheads between the 1996 and 2001 samplings (merged collections: female–77.5%, male–43.0%) and 2009–2011 (female–42.2%, male–13.6%). However, liver tumour prevalence in bullheads from the Anacostia, Potomac River (Washington, DC ) and Piscataway Creek (17 km downriver) was significantly higher than that for Chesapeake Bay watershed reference locations. The causes of skin tumours in bullheads are uncertain, requiring further research. The similar liver tumour prevalence in these three locations suggests that the problem is regional rather than restricted to the Anacostia. To monitor habitat quality and the success of pollution control actions, we recommend conducting tumour surveys on a 5‐year cycle coordinated with sediment chemistry analyses.

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Adverse events after screening and follow-up colonoscopy - Carolyn M. Rutter; Eric Johnson; Diana L. Miglioretti; Margaret T. Mandelson; John Inadomi; Diana S. M. Buist (Cancer Causes & Control, 2012)

Association between Antibiotic use Prior to Breast Cancer Diagnosis and Breast Tumour Characteristics (United States) - Christine M. Velicer; Susan R. Heckbert; Carolyn Rutter; Johanna W. Lampe; Kathi Malone (Cancer Causes & Control, 2006)

Olanzapine attenuates cue-elicited craving for tobacco - Kent E. Hutchison; Marie-Christine Rutter; Raymond Niaura; Robert M. Swift; Wallace B. Pickworth; Laura Sobik (Psychopharmacology, 2003)

β-Ketoacyl-acyl carrier protein synthase III from pea (Pisum sativum L.): properties, inhibition by a novel thiolactomycin analogue and isolation of a cDNA clone encoding the enzyme - Lesley A. Jones; Andy M. Gane; Derek Herbert; David L. Willey; Andrew J. Rutter; Peter Kille; Jane E. Dancer; John L. Harwood (Planta, 2003)

Colonoscopy aided by magnetic 3D imaging: assessing the routine use of a stiffening sigmoid overtube to speed up the procedure - G. D. Bell; R. S. Rowland; M. Rutter; M. Abu-Sada; S. Dogramadzi; C. Allen (Medical & Biological Engineering & Computing, 1999)

Increased concanavalin A capping in cells from brains of scrapie-infected hamsters - G. Rutter; D. M. Asher; R. G. Rohwer; C. J. Gibbs; D. C. Gajdusek (Archives of Virology, 1981)

Use of iodinated organic compounds for the density gradient centrifugation of viruses - H. H. Gschwender; G. Rutter; M. Popescu (Archives of Virology, 1975)